2006
DOI: 10.1097/01.mlg.0000230435.71328.b9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Skull Base Osteoradionecrosis After Radiotherapy for Nasopharyngeal Carcinoma

Abstract: Clinical diagnosis of skull base ORN was based on symptoms, computed tomography, or magnetic resonance imaging and endoscopy. The final confirmation was according to pathologic examination. Surgery had the best effect. Extensive ORN accompanied by radiation brain damage or cranial nerves damage had poor prognosis. Nasopharyngeal bleeding and exhaustion were the main causes of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
90
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 9 publications
3
90
0
Order By: Relevance
“…It has been reported that patients with NPC who receive 2 courses of radiation are more predisposed to having PRNN. 6,7 In this study, 50% (n ¼ 14) of the patients received 2 courses of radiotherapy to cure the local recurrent/persistent tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that patients with NPC who receive 2 courses of radiation are more predisposed to having PRNN. 6,7 In this study, 50% (n ¼ 14) of the patients received 2 courses of radiotherapy to cure the local recurrent/persistent tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a series study about osteoradionecrosis show that the dosage is highly related with the occurrence of skull base osteoradionecrosis. [7][8][9][10] Of 28 patients studied here, 14 patients received 2 courses of radiotherapy and the accumulating prescribed dose for the nasopharynx was more than 120 Gy. In the patients treated with IMRT, the dose for the nasopharynx was more than 80 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement may be classified as extensive and symmetric or localized. 46 Huang et al 46 concluded that histopathological evaluation is very important, as it is difficult to differentiate tumour recurrence from ORN at this site; with the two entities sometimes being co-existent.…”
Section: Skull Basementioning
confidence: 99%
“…Besides that, there can be dysphagia and/or respiratory distress. When the swelling is not visible externally, it may manifest as epistaxis and should alert the clinician for the possibility of a pseudoaneurysm of the cervical carotid artery [11]. …”
Section: Discussionmentioning
confidence: 99%